Obesogenic home food availability, diet, and BMI in Pakistani and White toddlers. Issue 3 (19th January 2021) - LeCroy, Madison N.; Bryant, Maria; Albrecht, Sandra S.; Siega‐Riz, Anna Maria; Ward, Dianne S.; Cai, Jianwen; Stevens, June
Abstract: Individuals of South Asian ethnicity have an increased risk for obesity and related diseases. Foods available in the home during the first 1000 days (conception to 24 months old) are an important determinant of diet, yet no study has examined the association of early‐life home food availability (HFA) with later diet and obesity risk in South Asian households. We examined whether obesogenic HFA at 18 months of age is associated with dietary intake and body mass index (BMI) at 36 months of age in low‐income Pakistani and White households in the United Kingdom. In this prospective birth cohort study (Born in Bradford 1000), follow‐up assessments occurred at 18 ( n = 1032) and 36 ( n = 986) months of age. Variety and quantity of snack foods and sugar‐sweetened beverages (SSBs) in the home and consumed were measured using the HFA Inventory Checklist and food frequency questionnaires, respectively. BMI was calculated using measured length/height and weight. Multinomial logistic regression models examined associations between HFA and tertiles of dietary intake, and multivariable linear regression models assessed associations between HFA and BMI. Pakistani households had a greater variety and quantity of snack foods and SSBs available compared with White households. Variety and quantity of snack foods and SSBs in the home at 18 months were positively associated with children's intake of these items at 36 months, but associations between HFA and BMI were null. Reducing obesogenic HFA during the first 1000 days may promote the development of more healthful diets, though this may not be associated with lower obesity risk during toddlerhood.